Water for food in Euphrates-Tigris river - Abdelmoneim Metwally; Mai M. Yasser; Merna Ahmed (Economies, 2024)
Water scarcity is an important threat to food security in the Euphrates-Tigris river. Water scarcity is a huge worldwide problem that results from the rapid increase in water demand, which exceeds the amount of available water. The most significant problems currently affecting countries are food insecurity water scarcity. The Euphrates-Tigris river countries suffer from different political issues, such as the Syrian war and internal civil conflicts in Iraq. In addition, this area consists of only three countries: Iraq, Syria, and Turkey, but it affects the entire Middle East. Turkey has established many irrigation projects compared to Iraq, which still suffers from the previous American invasion. Therefore, this study examines the Euphrates-Tigris river (using two countries) to examine the relationship between water scarcity and food security from 1992 to 2020. This study will be conducted using a fixed and random regression approach over 18 years. The results show a negative relationship between water scarcity and food security in the short run, at a 10% significance level, and a long-term positive relationship of 1%. Thus, the use of research and development and the encouragement of investments will help policymakers to develop a nexus between water scarcity and food security.
Keywords: 330; agriculture; development studies; Euphrates–Tigris river; food; urban development; water